A Comparison of CVR Magnitude and Delay Assessed at 1.5 and 3T in Patients With Cerebral Small Vessel Disease - Stringer, Michael S.; Blair, Gordon W.; Shi, Yulu; Hamilton, Iona; Dickie, David A.; Doubal, Fergus N.; Marshall, Ian M.; Thrippleton, Michael J.; Wardlaw, Joanna M. (Frontiers in Physiology, 2021)
Background Cerebrovascular reactivity (CVR) measures blood flow change in response to a vasoactive stimulus. Impairment is associated with several neurological conditions and can be measured using blood oxygen level-dependent (BOLD) magnetic resonance imaging (MRI). Field strength affects BOLD signal, but the effect on CVR is unquantified in patient populations. Methods We recruited patients with minor ischaemic stroke and assessed CVR magnitude and delay time at 3 and 1.5 Tesla using BOLD MRI during a hypercapnic challenge. We assessed subcortical grey (GM) and white matter (WM) differences using Wilcoxon signed rank tests and scatter plots. Additionally, we explored associations with demographic factors, white matter hyperintensity burden and SVD score. Results 18/20 patients provided usable data. At 3T versus 1.5T: mean CVR magnitude showed less variance (WM 3T: 0.062±0.018%/mmHg, range 0.035, 0.093; 1.5T: 0.057±0.024%/mmHg, range 0.016, 0.094) but was not systematically higher (Wilcoxon signal rank tests, WM: r=-0.33, confidence interval (CI): -0.013, 0.003, p=0.167); delay showed similar variance (WM 3T: 40±12s, range: 12, 56; 1.5T: 31±13s, range 6, 50), was shorter in GM (r=0.33, CI: -2, 9, p=0.164) and longer in WM (r=-0.59, CI: -16, -2, p=0.010). Patients with higher disease severity tended to have lower CVR at 1.5 and 3T. Conclusions Mean CVR magnitude at 3T was similar to 1.5T but showed less variance. GM/WM delay differences may be affected by low signal-to-noise ratio among other factors. While 3T may reduce variance in CVR magnitude CVR is readily assessable at 1.5T and reveals comparable associations and trends with disease severity.